Peningkatan Kompetensi Keseimbangan Ekosistem dengan Menggunakan Model Pembelajaran Problem Based Learning pada Peserta Didik Kelas V Sekolah Dasar - Pujantoro, Deni Condro (Universitas Sebelas Maret, 2020)
The study finds the background of delivering ecosystem balance matter hammed. Obstacles stem from the student’s low interest and poor selection of learning models. The research aims to provide a model of PBL learning in helping students to improve ecosystem balance competence. Stick to our previus research, so researchers assume that learning with an advanced PBL learning model could improve ecosystem balance competencies in class V SDN 3 Hargosari. There is an increased learning process, increased interest from pre-cycle to cycle II at 71,43%, and a 71,43% increase in learning from pre-cycle to cycle II. Thus, in order to obtain more qualified learning result, it will need to apply an advanced model of PBL learning to ecosystem balance materials study.